Regulation by Overlapping Promoters of the Rate of Synthesis and Deposition into Crystalline Inclusions of Bacillus thuringiensis δ-Endotoxins - Sedlak, Mira (American Society for Microbiology, 2000)
During sporulation, Bacillus thuringiensis produces intracellular, crystalline inclusions comprised of a mixture of protoxins active on insect larvae. A major class of these protoxin genes, designated cry1, is transcribed from two overlapping promoters (BtI and BtII) utilizing RNA polymerase containing sporulation sigma factors ς(E) and ς(K), respectively. Fusions of these promoters to lacZ were constructed in order to analyze transcription patterns. Mutations within the −10 region of the BtII promoter (within the spacer region of the BtI promoter) which departed from the consensus −10 sequence for either ς(E) or ς(K) resulted in inactivation of transcription from BtII and a fivefold stimulation of transcription from BtI. In contrast, transcription from both promoters was inhibited with a change to the ς(E) consensus. One of the “promoter-up” mutations was fused to the cry1Ac1 gene, and enhanced transcription was confirmed by Northern blotting. There was an increase in the accumulation of Cry1Ac antigen at early but not later times in sporulation in the mutant. This shift was due to the rapid turnover of much of the excessively accumulated protoxin at the early times as measured by pulse-chase labeling. As a result of the turnover and the inactivation of the BtII promoter, the mutant produced smaller inclusions which contained two- to threefold-less protoxin than inclusions from the wild type. Promoter overlap is a mechanism for modulating protoxin synthesis, thus ensuring the efficient packaging of these protoxins into inclusions.